End-user verification results of two serum separator tubes for clinical chemistry analytes according to CLSI GP34-A and CLSI GP41-A6 - Abusoglu, Sedat; Ecer, Busra; Guven, Halil; Yorulmaz, Ahmet Emre; Serdar, Muhittin Abdulkadir; Unlu, Ali; Akyurek, Fikret; Ozturk, Bahadir; Abusoglu, Gulsum (Scandinavian journal of clinical and laboratory investigation, 2024)
Tube manufacturers use different composition of gels and blood clot activator formulations in serum tube production. Our aim was to investigate the within-tube (repeatability) and between-tube variation, concordance between comparison results of BD and VacuSEL tubes. Blood samples were collected from control subjects (n = 20) and patients (n = 30) in accordance with the CLSI GP41-A6 and CLSI GP34-A guidelines. Twenty-three clinical chemistry parameters were analysed via Roche Cobas C702 Chemistry Analyzer on T0 (0 hour) and T24 (24 hour). Mean differences % were compared with Wilcoxon matched pair test. Clinical significance was evaluated based on desirable bias according to total allowable error (TEa). VacuSEL tubes demonstrated acceptable performance for the results of 20 parameters with regards to desirable bias % limits. Lactate dehydrogenase (LD) [mean difference % (%95 confidence intervals (CI) values of BD and VacuSEL tubes at T0 [6.41% (4.80-8.01%)]; sodium (Na) and total protein (TP) at T24 [-0.27% (-0.46 to -0.07%) and -1.39% (-1.87 to -0.91), respectively] were over the desirable bias limits (LD: 4.3%, Na: 0.23% and TP: 1.36%, respectively) but not exceeding total biological variation CV % [Na: 0.5 (0.0-1.0) % and TP: 2.6 (2.3-2.7) %). %95 confidence intervals (CI) of T0 LD values overlap with within-subject biological variation % (CI) limits (LD: 5.2 (4.9-5.4) %). The differences between two tubes were not medically significant and necessarily conclusive. VacuSEL serum tubes presented comparable performance with BD serum tubes.